The Effectiveness of Hybrid Guided Inquiry for Optimizing HOTS and Communication Skills in Circular Motion Concepts - Akhmad Jufriadi; Winda Agustina Rahayu; Hena Dian Ayu (Universitas Lambung Mangkurat, 2022)
This research was conducted to analyze the effectiveness of Hybrid Guided Inquiry on HOTS and students' communication skills in Circular Motion material. The method used in this research is quantitative research with a quasi-experimental. 10th-grade students of MIPA in SMA Negeri 1 Malang were used as the observed population; the samples taken were students 10 MIPA 2 and 10 MIPA 4. The MANOVA test is a technique used to test hypotheses and then analyze the effectiveness of H-GI in optimizing HOTS and students' communication skills. Analysis of the results of this study found that the HOTS score for the experimental class was 78.4 while for the control class was 71.1. Meanwhile, the communication skills results between the experimental class and the control class were 78 for the experimental class and 72 for the control class. Thus, H-GI is effective in optimizing HOTS and communication skills of students compared to direct learning, which uses PBL. The research results could be the basis for making learning more effective in physics material, especially the Circular Motion concepts.